Poststroke Cell Therapy of the Aged Brain - Aurel Popa-Wagner; Madalina Filfan; Adriana Uzoni; Pouya Pourgolafshan; Ana-Maria Buga (Neural Plasticity)
During aging, many neurodegenerative disorders are associated with reduced neurogenesis and a decline in the proliferation of stem/progenitor cells. The development of the stem cell (SC), the regenerative therapy field, gained tremendous expectations in the diseases that suffer from the lack of treatment options. Stem cell based therapy is a promising approach to promote neuroregeneration after brain injury and can be potentiated when combined with supportive pharmacological drug treatment, especially in the aged. However, the mechanism of action for a particular grafted cell type, the optimal delivery route, doses, or time window of administration after lesion is still under debate. Today, it is proved that these protections are most likely due to modulatory mechanisms rather than the expected cell replacement. Our group proved that important differences appear in the aged brain compared with young one, that is, the accelerated progression of ischemic area, or the delayed initiation of neurological recovery. In this light, these age-related aspects should be carefully evaluated in the clinical translation of neurorestorative therapies. This review is focused on the current perspectives and suitable sources of stem cells (SCs), mechanisms of action, and the most efficient delivery routes in neurorestoration therapies in the poststroke aged environment.